Plasmodium falciparum Kelch 13 mutations and treatment response in patients in Hpa-Pun District, Northern Kayin State, Myanmar. (December 2017) - Bonnington, Craig; Phyo, Aung; Ashley, Elizabeth; Imwong, Mallika; Sriprawat, Kanlaya; Parker, Daniel; Proux, Stephane; White, Nicholas; Nosten, Francois
Abstract Background Artemisinin resistance, linked to polymorphisms in the Kelch gene on chromosome 13 ofPlasmodium falciparum (k13 ), has outpaced containment efforts in South East Asia. For national malaria control programmes in the region, it is important to establish a surveillance system which includes monitoring fork13 polymorphisms associated with the clinical phenotype. Methods Between February and December 2013, parasite clearance was assessed in 35 patients with uncomplicatedP. falciparum treated with artesunate monotherapy followed by 3-day ACT in an isolated area on the Myanmar–Thai border with relatively low artemisinin drug pressure. Molecular testing fork13 mutations was performed on dry blood spots collected on admission. Results The proportion ofk13 mutations in these patients was 41.7%, and only 5 alleles were detected: C580Y, I205T, M476I, R561H, and F446I. Of these, F446I was the most common, and was associated with a longer parasite clearance half-life (median) 4.1 (min–max 2.3–6.7) hours compared to 2.5 (min–max 1.6–8.7) in wildtype (p = 0·01). The prevalence ofk13 mutant parasites was much lower than the proportion ofk13 mutants detected 200 km south in a much less remote setting where the prevalence ofk13 mutants was 84% with 15 distinct alleles in 2013 of which C580Y predominated. Conclusions This study provides evidence of artemisinin resistance in a remote part of eastern Myanmar. The prevalence ofk13 mutations as well as allele diversity varies considerably across short distances, presumably because of historical patterns of artemisinin use and population movements.